Associaton between Blood Total Testosterone Levels and Consolidated Memory on Eldery Men at Veterans Institution (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Decreased total testosterone levels in the blood will disrupt memory consolidation. In thisphase, one could still function normally even though it is difficult to recall the information that has beenlearned.Methods: The subjects were taken consecutively and conducted by interview, generalist, and neurologicalphysical examination, Word List Memory Task examination twice as well as measurement of totaltestosterone in the blood. The subjects were grouped into total blood testosterone levels of less than 298 ng/dl and more than equal to 298 ng/dl.Results: Fifty-four subjects studied obtained that total blood testosterone levels
Keywords: Elderly men, Total Testosterone in the Blood, Consolidation of Memory, Neurology